2022
DOI: 10.1093/nar/gkac216
|View full text |Cite
|
Sign up to set email alerts
|

MarcoPolo: a method to discover differentially expressed genes in single-cell RNA-seq data without depending on prior clustering

Abstract: The standard analysis pipeline for single-cell RNA-seq data consists of sequential steps initiated by clustering the cells. An innate limitation of this pipeline is that an imperfect clustering result can irreversibly affect the succeeding steps. For example, there can be cell types not well distinguished by clustering because they largely share the global structure, such as the anterior primitive streak and mid primitive streak cells. If one searches differentially expressed genes (DEGs) solely based on clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Therefore, we can draw similar conclusions about marker gene identification for these two methods of defining marker genes. We also found that MarcoPolo performed differently compared to the results in [14], despite conducting the same study using the same dataset. It is possible that MarcoPolo only used the genes with average expression levels in the top 30th percentile for data preprocessing, which may have led to some DEGs being ignored.…”
Section: The Identification Of Marker Genesmentioning
confidence: 71%
See 4 more Smart Citations
“…Therefore, we can draw similar conclusions about marker gene identification for these two methods of defining marker genes. We also found that MarcoPolo performed differently compared to the results in [14], despite conducting the same study using the same dataset. It is possible that MarcoPolo only used the genes with average expression levels in the top 30th percentile for data preprocessing, which may have led to some DEGs being ignored.…”
Section: The Identification Of Marker Genesmentioning
confidence: 71%
“…All three methods were developed for data for which cell clusters were not obvious to detect DEGs without prior clustering. Compared with other methods for detecting DEGs under two conditions, these three methods are faster and more accurate for DEG detection [13,14]. scMEB needs some non-DEGs to build the model; however, the ground truth of the genes is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations